Step-by-step explanation:
First, we need to graph the equality y = x² + 2x - 3
So, to graph the parabola, we need to identify the vertex and 2 points in the parabola.
The vertex can be calculated as:
![x=-(b)/(2a)=-(2)/(2(1))=-1](https://img.qammunity.org/2023/formulas/mathematics/college/ghr65wyt8ivcap33kzjd44relxh9ctfzqq.png)
Where b is the number beside the x and a is the number beside the x². Then the value of y is equal to:
![\begin{gathered} y=x^2+2x-3 \\ y=(-1)^2+2(-1)-3 \\ y=1-2-3 \\ y=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qb4uxir74fw7awhtgx5teecjk66oh28r7l.png)
So, the vertex (- 1, - 4)
Then, to find 2 points in the parabola we can replace x by 0 and x by -2 as:
For x = 0
![\begin{gathered} y=x^2+2x-3 \\ y=0^2+2\cdot0-3 \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/phvd45m1kkxfmtigh9k3rnohdfz2g7la57.png)
For x = -2
![\begin{gathered} y=(-2)^2+2\cdot(-2)-3 \\ y=4-4-3=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e12nowz4tmhjh4mrw4qav8xx234b9b4j9o.png)
Therefore, we have the vertex (-1, -4) and the points (0, -3) and (-2, -3)
Then, the inequality is y less or equal than the parabola so, the zone for the inequality is:
So, the graph of the inequality is the region below the graph of the parabola.